2006
DOI: 10.1037/0090-5550.51.3.202
|View full text |Cite
|
Sign up to set email alerts
|

The development and psychometric validation of the Disability Attitude Implicit Association Test.

Abstract: and demographics. Results: DA-IAT congruent associations (disability plus negative-nondisabled plus positive) occurred more frequently than incongruent associations (disability plus positive-nondisabled plus negative). DA-IAT had no relationship with the Attitude Toward Disabled Persons Scale, an explicit attitude measure. Demographics did not predict DA-IAT scores. Contact with Disabled Persons Scale was the dominant predictor for the DA-IAT. Conclusions: The DA-IAT has the potential to become a useful measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
148
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(161 citation statements)
references
References 63 publications
(91 reference statements)
10
148
0
2
Order By: Relevance
“…As described by Pruett and Chan (2006), when professional carers feel pressure to outwardly express attitudes in line with what is thought to be socially appropriate while attempting to overcome negative biases and assumptions, this can lead to symptoms of burnout and other psychological problems (see Maslach, Jackson, & Leiter 1996). It seems likely that such effects would be most pronounced for thoughts and feelings that are deemed to be negative, as opposed to thoughts and feelings that fail to confirm some level of positivity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As described by Pruett and Chan (2006), when professional carers feel pressure to outwardly express attitudes in line with what is thought to be socially appropriate while attempting to overcome negative biases and assumptions, this can lead to symptoms of burnout and other psychological problems (see Maslach, Jackson, & Leiter 1996). It seems likely that such effects would be most pronounced for thoughts and feelings that are deemed to be negative, as opposed to thoughts and feelings that fail to confirm some level of positivity.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the research concerning the automaticity of negative attitudes or prejudices (see Pruett & Chan, 2006) and its relationship to behaviour, Akrami et al (2006) acknowledged that any future research on attitudes towards individuals with developmental or intellectual disabilities should focus on ''examining these attitudes' more implicit or automatic function using an experimental design analyzing implicit rather than explicit attitudes'' (p. 615). They suggested that the assessment of attitudes using implicit measures was an important step in understanding what impact the label or social category of people with disabilities has on our implicit attitudes, and furthermore, on our behaviour and social interactions.…”
mentioning
confidence: 99%
See 3 more Smart Citations